2019
DOI: 10.3390/plants8070214
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Role of the WRKY Gene Family under Stress Conditions in Pigeonpea (Cajanus Cajan L.)

Abstract: Pigeonpea (Cajanus cajan L.), a protein-rich legume, is a major food component of the daily diet for residents in semi-arid tropical regions of the word. Pigeonpea is also known for its high level of tolerance against biotic and abiotic stresses. In this regard, understanding the genes involved in stress tolerance has great importance. In the present study, identification, and characterization of WRKY, a large transcription factor gene family involved in numerous biological processes like seed germination, met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 88 publications
0
9
0
Order By: Relevance
“…WRKY transcription factor genes, known as the largest gene family in higher plants, have been reported in many species including Arabidopsis , rice, tomato, cotton, pineapple and wild strawberry [ 39 ]. Massive studies have indicated the regulatory role of WRKY gene members that confers biotic as well as abiotic stress tolerance to crop plants [ 40 ]. Heat shock proteins (HSPs), often performing chaperone functions [ 41 ], express not only in response to various stresses [ 42 , 43 , 44 , 45 ], but also exhibit developmental and clinical significances [ 46 , 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…WRKY transcription factor genes, known as the largest gene family in higher plants, have been reported in many species including Arabidopsis , rice, tomato, cotton, pineapple and wild strawberry [ 39 ]. Massive studies have indicated the regulatory role of WRKY gene members that confers biotic as well as abiotic stress tolerance to crop plants [ 40 ]. Heat shock proteins (HSPs), often performing chaperone functions [ 41 ], express not only in response to various stresses [ 42 , 43 , 44 , 45 ], but also exhibit developmental and clinical significances [ 46 , 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The WRKY genes play a significant role in regulating several processes in plants (Chen et al, 2012;Yu et al, 2010). The WRKY proteins, based on the WRKY domain numbers and zing-finger pattern/signature have been classified in three groups; group I, group II and group III (Singh et al, 2019;Yu et al, 2010). The WRKY proteins belonging to group I have two domains and a C2H2 zinc-finger signature.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we selected three WRKY-DBDs representing three different variants that belong to different groups [47]. The CcWRKY1belongedto group I, having two WRKY DBDs, one at N-terminal and another at C-terminal, while only the C-terminal WRKY domain took part in the sequence-specific DNA-binding process, thus the C-terminal domain of CcWRKY1 was considered Type I WRKY-DBD.…”
Section: Sequence Analysis and Comparative Phylogenymentioning
confidence: 99%
“…Pigeonpea crop has vital importance in food and nutritional security since it provides a rich source of proteins, vitamins, and minerals for more than a billion of the population in the developing world [45,46]. According to Food and Agriculture Organization [47] statistics, the estimated common cropping area under the pigeonpea cultivation was approximately 7.03 million hectares in 2018 with a production of 4.89 million tons and an average yield of 695Kg/ha. Considering the cropping area and the production of pigeonpea, India ranks first in the world, which accounts for approximately sixty-six percent of total pigeonpea production.…”
Section: Introductionmentioning
confidence: 99%